40th AIAA Aerospace Sciences Meeting &Amp; Exhibit 2002
DOI: 10.2514/6.2002-584
|View full text |Cite
|
Sign up to set email alerts
|

Plug nozzles: summary of flow features and engine performance - Overview of RTO/AVT WG 10 subgroup 1

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…However, technological difficulties in the development of the aerospike nozzle made it fall behind the development of conventional nozzle and research on the aerospike nozzle stagnated. In the 1990s, much attention was devoted to this nozzle concept and intensive studies on the aerospike nozzle were carried out again in the United States [1,2], Europe [3], Japan [4,5], Russia [6,7] and China [8]. Because of overweight composite cryogenic fuel tank and high cost, X-33 vehicle plan was called off eventually, however, full-size linear aerospike engine was produced and hot-firing tested at sea level successfully.…”
Section: Introductionmentioning
confidence: 99%
“…However, technological difficulties in the development of the aerospike nozzle made it fall behind the development of conventional nozzle and research on the aerospike nozzle stagnated. In the 1990s, much attention was devoted to this nozzle concept and intensive studies on the aerospike nozzle were carried out again in the United States [1,2], Europe [3], Japan [4,5], Russia [6,7] and China [8]. Because of overweight composite cryogenic fuel tank and high cost, X-33 vehicle plan was called off eventually, however, full-size linear aerospike engine was produced and hot-firing tested at sea level successfully.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the recent years, a renewed interest in the aerospike nozzle flowfield has been generated for both rocket and aeronautic applications. [2][3][4][5][6] However, while flow separation in over-expanded planar or bell ideal and optimized contour nozzles has been widely investigated to elucidate the phenomenon of boundary layer separation and shock interactions, aerospike nozzles have received little attention in the frame of this study. Verma 4 and Kapilavai et al 7 presented pioneering work upon flow separation behavior in aerospike nozzles that operated at NPRs below 10, and both of the two studies indicated that the presence of flow phenomenon was associated with nozzle flow separation, and unsteady shock oscillation induced by the interaction of the shock/boundary layer seen in conventional supersonic nozzles with diverging sections could also be expected in aerospike nozzles at off-design operating NPRs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies point out these benefits in detail 17,23 and discuss proper flow expansion of an aerospike. 19,22 The self-adjusting feature of an aerospike engine only occurs at altitudes below the engine design altitude. Above this point, the engine performs similar to a conventional bell nozzle, which is why an aerospike engine should be designed with a design altitude as high as possible.…”
Section: Introductionmentioning
confidence: 99%